Effects of the Staphylococcus aureus and Staphylococcus epidermidis Secretomes Isolated from the Skin Microbiota of Atopic Children on CD4+ T Cell Activation - Laborel-Préneron, Emeline; Bianchi, Pascale; Boralevi, Franck; Lehours, Philippe; Fraysse, Frédérique; Morice-Picard, Fanny; Sugai, Motoyuki; Sato'o, Yusuke; Badiou, Cédric; Lina, Gérard; Schmitt, Anne-Marie; Redoulès, Daniel; et al. (PloS one, 2015)
Interactions between the immune system and skin bacteria are of major importance in the pathophysiology of atopic dermatitis (AD), yet our understanding of them is limited. From a cohort of very young AD children (1 to 3 years old), sensitized to Dermatophagoides pteronyssinus allergens (Der p), we conducted culturomic analysis of skin microbiota, cutaneous transcript profiling and quantification of anti-Der p CD4+ T cells. This showed that the presence of S. aureus in inflamed skin of AD patients was associated with a high IgE response, increased expression of inflammatory and Th2/Th22 transcripts and the prevalence of a peripheral Th2 anti-Der p response. Monocyte-derived dendritic cells (moDC) exposed to the S. aureus and S. epidermidis secretomes were found to release pro-inflammatory IFN-γ and anti-inflammatory IL-10, respectively. Allogeneic moDC exposed to the S. aureus secretome also induced the proliferation of CD4+ T cells and this effect was counteracted by concurrent exposure to the S. epidermidis secretome. In addition, whereas the S. epidermidis secretome promoted the activity of regulatory T cells (Treg) in suppressing the proliferation of conventional CD4+ T cells, the Treg lost this ability in the presence of the S. aureus secretome. We therefore conclude that S. aureus may cause and promote inflammation in the skin of AD children through concomitant Th2 activation and the silencing of resident Treg cells. Commensals such as S. epidermidis may counteract these effects by inducing the release of IL-10 by skin dendritic cells.